Analysis Regarding Brand Dispute Cases Based on Case Study of Decision Number 4 Pk/Pdt.Sus-Hki/2023 - Jeane Neltje Saly; Ivana Trixie; Margaretha Putri; Pricillia Imanuela; Angeline Wellvy Santoso (CV. Rayyan Dwi Bharata, 2023)
Brand is a very important thing for the business world, especially for business people, because the brand is the identity of a product or company that is very valuable. A well-known brand from the United States, namely TIMBERLAND, is in dispute with a local brand, namely TIMBERLAKE, judging from the sentence that dominates the word